Perda Progressive : an Alternative To Fulfillment of Poor People Rights of Health in Local Autonomy - H.S. Tisnanta; Agus Triono (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Autonomy system based on act No. 32 /2004 directed the effort to accelerate the realization of thepeople's welfare. Level of welfare can be measured through human development index consist of twomain indicators, that are health and the economy. Autonomy will be encourage government localaccountability and increased sensitivity to provide public goods and services. Accountability andsensitivity of local government based on Perdawhich is form of local legislation.However, the fact shown that there has been a gap between perda and social condition materialized inthe form of poverty. Perda can not guarantee the health rights for the poor in term of freedom,availability, affordability, acceptability and quality. In addition, there is lack on the quantity of perdaand quality of perdas a legal framework to ensure the good services provided by local government.The fulfillment of the health poor rights is requiring progressive perda encompassing the aspects ofauthority, procedure and substance of perda. The moralityof perda progressive can be achieved throughthe empowerment for the poor using a rights-based approach. The empowerment shall be conductedthrough the formulation of perda progressive aiming right enhancement, rights awareness, rightsenablement, and rights enforcement. The effort is requiring the principles of responsiveness, as theprinciple of material formulation and implementation of perda progressive, within the framework ofpurposive law